Two-Stage Synthesis of Bournonite cupbsbs3 Thin Films for Photovoltaic Applications - Radhalayam, D (ELSEVIER SCI LTD, 2026)
Bournonite (CuPbSbS3) exhibits promising characteristics as a photovoltaic light harvester. However, the solution-based methods commonly employed for its synthesis and device fabrication have prompted the exploration of physical vapor deposition (PVD) techniques. In this study, CuPbSbS3 thin films and corresponding solar cells were synthesized using a two-stage approach: thermal evaporation of Sb/Cu/Pb/Cu metal precursors followed by sulfurization. The effect of sulfurization duration (5-30 min) on the growth and physical properties of the Bournonite thin films was systematically investigated. Films sulfurized for a short duration of 5 min exhibited minor PbS and CuSbS2 secondary phases, crystallite sizes of approximately 68.1 nm, and grain sizes ranging from 0.5 to 1.0 mu m. Increasing the sulfurization duration to 10-30 min eliminated the PbS secondary phase, improved stoichiometry and crystallinity (up to 71 nm), and resulted in larger grains (1.0-1.5 mu m). The films demonstrated high optical absorption coefficients exceeding 104 cm-1 in the visible region and a direct bandgap of 1.37-1.41 eV. Thin-film solar cells fabricated using these absorber layers showed a decrease in performance with longer sulfurization times, attributed to reduced carrier mobility. As the sulfurization duration increased from 5 to 30 min, the device efficiency dropped from 0.13% to 0.08%, short-circuit current density (Jsc) from 1.59 to 1.28 mA/cm2, open-circuit voltage (Vcc) from 269.1 to 220.9 mV, and fill factor (FF) from 29.6% to 26.6%. These promising initial results establish a foundation for the development of high-efficiency Bournonite thin-film solar cells using PVD techniques.